Measuring the Ecosystem Impacts of Commercial Shrimp Trawling and Other Fishing Gear in Core Sound, North Carolina Using Ecological Network Analysis - Deehr, Rebecca A. (East Carolina University, 2012)
The impacts of commercial trawling are well documented, especially alteration of benthic environments, removal of targeted and by-catch species, and alteration of food webs. I investigated and modeled the impacts of shrimp trawling on the estuarine ecosystem in Core Sound, North Carolina. Since 1978, the North Carolina Division of Marine Fisheries has enforced no-trawling rules in nursery areas, but most of Core Sound is open to trawling. This "natural experiment" allowed me to compare the ecosystem impacts trawling using ecological network models. I used field collections, fisheries data from the NC Trip Ticket program, and Ecopath network modeling software to create four network models of areas open and closed to shrimp trawling during spring (2007) and fall (2006 and 2007). Each model consisted of 65 compartments (including non-living detritus, by-catch, producers, and various invertebrate and vertebrate consumers), and harvests by different types of fishery gears (crab pots, gill nets, haul seines, and pound nets in closed areas; shrimp trawls, skimmer trawls were added to the models in areas open to trawling). Approximately 12,000 shrimp trawling trips occurred from 2001 - 2007 in areas open to trawling, suggesting the potential for large trawling impacts. Based on the benthic sampling, shrimp trawling had a major impact on the Core Sound ecosystem. Contrary to expectation, biomass (g C/m²) of infaunal benthic invertebrates, especially deposit-feeding polychaetes, was significantly greater in areas open to trawling. Meiofaunal biomass was significantly greater in the closed areas. Field collections of fish and invertebrates revealed that there was more biomass (g C/m²) of benthic-invertebrate feeders (such as spot, pinfish and blue crabs) in areas closed to trawling. These results suggest a trophic cascade due to trawling may have occurred in the open areas, whereby trawls removed benthic-feeding fishes and blue crabs, released their prey (benthic polychaetes) from predation pressure, and lowered the abundance of meiofauna (prey of the polychaetes). Alternatively, the dead biomass from by-catch could fuel the growth in polychaetes and other benthos due to a direct subsidy from trawling. Further experimental work is required to test these model-derived hypotheses. Ecopath outputs were validated using stable isotopes and examined for system-wide impacts. The concentrations of stable isotopes of [delta]¹⁵N and [delta]¹³C were compared to Ecopath effective trophic levels. Trophic fractionation occurred across trophic levels, and results were comparable to published studies (for each unit effective trophic level increase there was a fractionation of +2.637% for [delta]¹⁵N and +1.084% for [delta]¹³C). Ecopath whole-ecosystem metrics indicated that net primary productivity, trophic efficiency, ascendency, and net primary production: respiration ratios were greater in the areas open to trawling; total system throughput and Finn Cycling Index were greater in the areas closed to trawling. Additional compartment-level comparisons were made using mixed trophic impacts (MTI) and keystoneness index (KSI). The MTI analysis indicated that shrimp trawling in Core Sound caused large negative impacts only on jellyfish, a bycatch species. The KSI indicated that sea turtles and brown pelicans were keystone groups (large influence relative to their biomass) overall in Core Sound. Spot, bluefish and Atlantic croaker also had high KSI in closed areas. Pink shrimp, white shrimp and bluefish all had high KSIs in the open areas, suggesting that they played a key role in the ecosystem's trophic structure where trawling was allowed. These Ecopath models can be useful tools for resource managers to better understand the direct and indirect impacts of (shrimp trawl) fishing in Core Sound. Future work should include the creation of annualized models and simulation modeling using Ecosim to explore different management scenarios.
Keywords: Ecology; Ecological network analysis; Ecopath; Nursery areas; Shrimp trawling; Stable isotopes; Biology, Ecology; Trawls and trawling--North Carolina--Core Sound; Trawls and trawling--Bycatches--North Carolina--Core Sound; Marine ecology--North Carolina--Core Sound; Shrimp populations--North Carolina--Core Sound; Benthos--North Carolina--Core Sound; Core Sound (N.C.)